On Refinements of Multidimensional Inequalities of Hardy-Type via Superquadratic and Subquadratic Functions. (24th November 2022) - Zakarya, M.; AlNemer, Ghada; Abd El-Hamid, H. A.; Butush, Roqia; Rezk, H. M.
Abstract : By utilizing the peculiarities of superquadratic and subquadratic functions, we give the extensions for multidimensional inequalities of Hardy-type with general kernel. We use some algebraic inequalities such as the Minkowski inequality, the refined Jensen inequality, and the Bernoulli inequality to prove the essential results in this paper. The performance of the superquadratic functions is reliable and effective to obtain new dynamic inequalities on time scales. By utilizing special kernels, we also acquire numerous examples and implementations of the related inequalities.